Methodical approaches to monitoring local democracy: purpose, classification, content - D.O. (Економіка, управління та адміністрування, 2023)
Monitoring of local democracy is an important component of effective decision-making in the field of public administration as it forms the public trust in democracy. There are a number of methodological approaches to the analysis of local democracy in the world developed and used by international organizations and agencies, teams of scientists and researchers. The article systematizes a significant number of methods of monitoring local democracy. They are grouped with the results of research not only in local democracy, but also in terms of its development. The characteristics are considered and examples of methods of measuring democracy in the country, methods of monitoring political systems, methods of monitoring the democracy of public administration and methods of analysis of local government are given. Methods of measuring democracy in the country provide a comprehensive nature of monitoring and the results of indicators that characterize historical, economic, political and other processes. A condition for the dynamic development of local democracy is the development of the country’s political system based on democratic principles and the effectiveness of the public level at all levels. That is why the article systematizes the methods that allow determining the country’s progress in the formation of systemic conditions for the development of democracy. The main attention is paid to the methods of measuring local democracy, which allows to study the democratic nature of local governance, the strength and quality of local democracy, the level of use of e-technologies. The study of existing methods in terms of their content, advantages and disadvantages of application allows users to determine those approaches that will allow to obtain the most objective results of the analysis, to conduct comparisons across individual countries, territories and cities, as well as to identify problematic areas of lagging behind best practices.